The Influence of Accounting Understanding, Education Level, and Quality of Village Apparatus Job Training on Understanding Village Financial Reports - Pramudita Putri Rizqianti; Hadiah Fitriyah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of Accounting Understanding, Education Level, and Quality of Village Apparatus Training on Understanding Village Financial Reports. This research method uses quantitative. The sampling technique used purposive sampling as many as 60 village officials by distributing questionnaires to 20 villages in Prambon sub-district. The data analysis technique used is validity and reliability test and multiple linear regression analysis. T test (partial test) and multiple determination coefficient test (R²) to test the hypothesis with SPSS version 26 program. The results of this study indicate that (1) understanding of accounting affects understanding of village financial statements, (2) level of education affects understanding of financial statements village, and (3) the quality of village apparatus job training affects the understanding of village financial reports.